Drug Prevention Among Youth in Wael Village - Anwar, Arman; La Uri, Leja Ishak; Gailea, Muhamad Eksal; Katima, Nurul (AIWADTHU: Jurnal Pengabdian Hukum, 2026)
Introduction: The issue of narcotics or drugs in developing countries goes hand in hand with changes in the global order. Because drugs are an urgent problem, their distribution must be stopped. To combat drug distribution, the process must be carried out systematically and in a planned manner. The handling of this issue must be carried out from the central to regional levels. Purposes of The Devotion: To provide young people with an understanding and knowledge of the dangers of drugs and their consequences, both in terms of the law and health. Method of The Devotion: Based on the community service paradigm, the study on the socialization carried out in Wael Hamlet used the Participatory Action Research (PAR) approach, which is an approach that aims to learn how to overcome problems and fulfill the practical needs of the community. Results Main Findings of the Devotion: Through the theme of the dangers of drug abuse, the youth listened very seriously to the presentations given by the speakers. The issue of the dangers of drugs not only aroused a serious attitude but also built a critical attitude among the youth of Wael Hamlet towards the impact of drugs on their future. Discourse clearly emerged during the speaker's presentation and the question and answer session.